2019
DOI: 10.7554/elife.37227
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining and maintaining cortical hand representation as evidenced from acquired and congenital handlessness

Abstract: A key question in neuroscience is how cortical organisation relates to experience. Previously we showed that amputees experiencing highly vivid phantom sensations maintain cortical representation of their missing hand (Kikkert et al., 2016). Here, we examined the role of sensory hand experience on persistent hand representation by studying individuals with acquired and congenital hand loss. We used representational similarity analysis in primary somatosensory and motor cortex during missing and intact hand mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
129
4

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(149 citation statements)
references
References 85 publications
16
129
4
Order By: Relevance
“…One would expect cortical remapping to occur in the case of spinal cord injury; however, current models of remapping predict that the immediately adjacent intact body parts (in this case face and head) should become more dominant (Qi, Stepniewska, and Kaas 2000). Instead, we found in participant T5 that arm and leg movements were more strongly represented than face and head movements, suggesting that the extent of remapping may be limited in precentral gyrus; consistent with this, a recent fMRI study also found limited motor cortical remapping in hand amputees (Wesselink et al 2019). The fact that we observed roughly the same proportions of modulation for face, head, arm and leg movements in participant T7, who had ALS, gives further confidence that the broad tuning we observed was not caused by remapping.…”
Section: Discussionsupporting
confidence: 88%
“…One would expect cortical remapping to occur in the case of spinal cord injury; however, current models of remapping predict that the immediately adjacent intact body parts (in this case face and head) should become more dominant (Qi, Stepniewska, and Kaas 2000). Instead, we found in participant T5 that arm and leg movements were more strongly represented than face and head movements, suggesting that the extent of remapping may be limited in precentral gyrus; consistent with this, a recent fMRI study also found limited motor cortical remapping in hand amputees (Wesselink et al 2019). The fact that we observed roughly the same proportions of modulation for face, head, arm and leg movements in participant T7, who had ALS, gives further confidence that the broad tuning we observed was not caused by remapping.…”
Section: Discussionsupporting
confidence: 88%
“…Traditionally, body representation in the sensorimotor cortex is considered to be highly adaptive even in the adult brain (26,27) however recent research contributes a new perspective on its malleability (12,13). Tools have been suggested to update the biological body representation, for example by tool-body integration (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…It is highly consistent within (8) and across (9) participants and is preserved even after severe loss of motor functions due to e.g. stroke (9), spinal cord injury (10), disability (11) or even hand amputation (12)(13)(14). Hand representation has been suggested to reflect daily hand use (9), with studies showing that it may be altered under constrained circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…Digit somatotopy is characterised in neuroimaging by two main principles: 1) digit selectivity, meaning separable regions show increased responsiveness to one digit compared to all other digits , and 2) inter-digit overlap, where neighbouring digits are more overlapping in their representation than non-neighbouring digits (Ejaz et al, 2015). The features of these digits maps have been extensively studied separately using either active (Kikkert et al, 2016;Wesselink et al, 2019) or passive tasks (Martuzzi, van der Zwaag, Farthouat, Gruetter, & Blanke, 2014;Sanchez-Panchuelo et al, 2010;Schweizer, Voit, & Frahm, 2008). Recent work by Berlot and colleagues (2019) provided a comparison between active and passive tasks.…”
Section: Introductionmentioning
confidence: 99%